NR4A1 Deletion in Marginal Zone B Cells Exacerbates Atherosclerosis in Mice—Brief Report. Issue 11 (November 2020) - Nus, Meritxell; Basatemur, Gemma; Galan, Maria; Cros-Brunsó, Laia; Zhao, Tian X.; Masters, Leanne; Harrison, James; Figg, Nichola; Tsiantoulas, Dimitrios; Geissmann, Frederic; Binder, Christoph J.; Sage, Andrew P.; et al.
Abstract : Objective: NR4A orphan receptors have been well studied in vascular and myeloid cells where they play important roles in the regulation of inflammation in atherosclerosis. NR4A1 (nerve growth factor IB) is among the most highly induced transcription factors in B cells following BCR (B-cell receptor) stimulation. Given that B cells substantially contribute to the development of atherosclerosis, we examined whether NR4A1 regulates B-cell function during atherogenesis. Approach and Results: We found that feeding Ldlr −/− mice a Western diet substantially increased Nr4a1 expression in marginal zone B (MZB) cells compared with follicular B cells. We then generated Ldlr −/− mice with complete B- or specific MZB-cell deletion of Nr4a1 . Complete B-cell deletion of Nr4a1 led to increased atherosclerosis, which was accompanied by increased T follicular helper cell–germinal center axis response, as well as increased serum total cholesterol and triglycerides levels. Interestingly, specific MZB-cell deletion of Nr4a1 increased atherosclerosis in association with an increased T follicular helper–germinal center response but without any impact on serum cholesterol or triglyceride levels. Nr4a1 −/− MZB cells showed decreased PDL1 (programmed death ligand-1) expression, which may have contributed to the enhanced T follicular helper response. Conclusions: Our findings reveal a previously unsuspected role for NR4A1 in the atheroprotective role of MZB cells. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.